Characterization of novel peptide-specific antibodies against the translation elongation factor eEF1A2 and their application for cancer research - Shalak, V.F.; Vislovukh, A.A.; Novosylna, O.V.; Khoruzhenko, A.I.; Kovalenko, M.I.; Kolesanova, E.F.; Egorova, E.A.; Mishin, A.A.; Krotevych, M.S.; Skoroda, L.V.; Negrutskii, B.S. (Вiopolymers and Cell, 2014)
Aim. We intend to characterize the new peptide-specific antibodies against the isoform 2 of translation elongation factor 1A (eEF1A2) and determine its presence in the postoperative samples of human breast, lung and stomach tumor tissues. Methods. The analysis of antibody specificity was performed by enzyme-linked immunosorbent assay, immunoblotting and immunohistochemistry. Immunoblotting and immunohistochemistry were used for the determination of the eEF1A2 in the human tumor samples, as well as in the samples of normal tissues surrounding tumors. Results. The antibodies obtained against the eEF1A2 specifically recognized this protein in the cell extracts and histological sections and did not cross-react with the elongation factor 1A isoform 1. eEF1A2 was revealed in the postoperative samples of breast, lung and stomach tumors as well as in the putative normal tissues surrounding tumors. Conclusions. The antibodies obtained against eEF1A2 are highly specific for the antigen and can be used for the immunological studies of tumors.